The Effect of Warm Compress on the Intensity of Back Pain in Pregnant Women in the Third Trimester: Scoping Review - Ayu, Bella Riska (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: Pregnancy is a natural process. During pregnancy, a mother experiences discomfort, one of which is back pain, there are several treatments to treat back pain, namely pharmacological and non-pharmacological therapies. One of the nonpharmacological therapies that can be done is with warm compresses because it is safer, cheaper, effective, cheap and without adverse effects.Purpose : This article aims to identify literature related to the effect of warm compresses on the intensity of back pain in pregnant women in the third trimester.Methods: The method used is scoping review which consists of 5 phases, namely identifying scoping review questions using the PICO framework; identifying relevant articles; searching for articles using relevant databases, namely PubMed, Wiley, and Google Scholar; creating PRISMA flowcharts; conducting critical appraisals to assess the quality of articles; charting data; compiling, summarizing and reporting results.Results: The results of the review of 15 selected articles obtained 8 articles with grade A, 7 articles grade B, 11 articles using quasi experiment, and 4 articles pre experiment. Two themes that emerged based on the results of the Scoping Review are the concept of back pain, and the concept of warm compresses.Conclusion: Warm compresses are effective in reducing back pain in pregnant women in the third trimester, so they can be recommended as complementary therapy to reduce the intensity of back pain.